Fighting Terrorism is A Community Devotion of College in Accordance with Its Tri Dharma Mandates - Irisa Iradati; Difa Wardatul Izza; Lintang Kusumo; Faizi Endarta; Patria Erlangga (Journal La Sociale, 2020)
Indonesia legislative assembly has legalized the Law Number 5 of 2018 concerning the Stipulation of Government Regulation instead of the Law Number I of 2002 concerning the Eradication of Terrorism Crimes into Law. Even so, the practice of which has experienced many obstacles that it has not so far been effective in countering terrorism in Indonesia. Counter terrorism efforts cannot be viewed, conceptualized and carried out in a sector manner by legal institutions only. A National Terrorism Eradication Institution called BNPT is already built by the government to practice this law but seeing the obstacles of the practice faced, it still needs to be systemically strengthened, empowered and better-coordinated by the Coordinating Ministry of Politics, Law and Security. While its efforts in eradicating terrorism need to be systematically designed as a single entity, integrated and interacted with those of various other related institutions, periodically measured and sustained until the strategic objectives are achieved optimally. College as a public institution, in accordance with its Tri Dharma mandates, as education, research and community service development, is obliged to initiate and play a more active and creative role as one of the supporting elements of the National Terrorism Eradication Institution in a Total System Approach. While legal institutions shall remain as the leading sector since all counter terrorism efforts are dominantly parts of law enforcement efforts. This study uses the normative-empirical method with the Total System concept approach and statue approach. The purpose of this study is to analyze counter-terrorism efforts in a preventive sociological and repressive manner.